Chromogranin A as a biomarker of disease activity and biologic therapy in inflammatory bowel disease: a prospective observational study. (August 2014) - Zissimopoulos, Athanasios; Vradelis, Stergios; Konialis, Manolis; Chadolias, Dimitrios; Bampali, Asimenia; Constantinidis, Theodoros; Efremidou, Eleni; Kouklakis, George
Abstract Objective. To access the correlation of Chromogranin A (CgA) with inflammatory bowel disease (IBD) activity and responsiveness to medical therapy. Material and methods. A prospective observational study was conducted in 56 patients with moderate ulcerative colitis (UC) or Crohn's disease (CD) (UC, n = 29, CD, n = 27), 17 patients with irritable bowel syndrome and predominant diarrhea (IBS-D) and 40 healthy volunteers. IBD patients were treated by biologics (infliximab or adalimumab) or conventional agents (aminosalicylates, thiopurines or methotrexate and steroids) and were classified according to their treatment in two groups. Serum CgA was measured at baseline and 4-week posttreatment period. Results. Serum CgA was significantly higher in IBD patients than in those with IBS-D or healthy volunteers (p < 0.01). Furthermore, serum CgA was markedly increased in CD patients than in UC patients (p < 0.01). CgA value was significantly reduced in 'biologic' group (24 IBD patients, UC, n = 15, CD, n = 9) at 4-week posttreatment period (p < 0.01), while 18/24 (72%) patients were already in remission during that time. In contrast, CgA value was significantly increased in the 'conventional' treatment group (32 IBD patients, UC, n = 14, CD, n = 18) between the two visits (p < 0.01), although 22/32 (69%) patients were in remission during the 4-week posttreatment period. Conclusion. CgA appears to be a reliable marker of disease activity in IBD patients and especially in those who received biologic therapy. IBS-D patients presented normal CgA values.